TMEM16A, a Homoharringtonine Receptor, as a Potential Endogenic Target for Lung Cancer Treatment - Guo, Shuai; Bai, Xue; Shi, Sai; Deng, Yawen; Kang, Xianjiang; An, Hailong (International journal of molecular sciences, 2021)
Lung cancer has the highest rate of incidence and mortality among all cancers. Most chemotherapeutic drugs used to treat lung cancer cause serious side effects and are susceptible to drug resistance. Therefore, exploring novel therapeutic targets for lung cancer is important. In this study, we evaluated the potential of TMEM16A as a drug target for lung cancer. Homoharringtonine (HHT) was identified as a novel natural product inhibitor of TMEM16A. Patch-clamp experiments showed that HHT inhibited TMEM16A activity in a concentration-dependent manner. HHT significantly inhibited the proliferation and migration of lung cancer cells with high TMEM16A expression but did not affect the growth of normal lung cells in the absence of TMEM16A expression. In vivo experiments showed that HHT inhibited the growth of lung tumors in mice and did not reduce their body weight. Finally, the molecular mechanism through which HHT inhibits lung cancer was explored by western blotting. The findings showed that HHT has the potential to regulate TMEM16A activity both in vitro and in vivo and could be a new lead compound for the development of anti-lung-cancer drugs.